2014
DOI: 10.1111/ijd.12454
|View full text |Cite
|
Sign up to set email alerts
|

Huntingtin interacting protein 1 as a histopathologic adjunct in the diagnosis of Merkel cell carcinoma

Abstract: Comparing the results of HIP1 and CK20, there were four discordant pairs (three positive for CK20 but negative for HIP1 and one positive for HIP1 but negative for CK20). McNemar's test indicated that there was no statistical significance (P = 0.625), thereby implying a close agreement between the expression of HIP1 and CK20 in these neuroendocrine neoplasms.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
9
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 16 publications
0
9
0
Order By: Relevance
“…In addition to the conditional nature of this allele that allows for expression of HIP1 in specific tissues at specific times, there were other potential advantages of this targeting strategy. First, since HIP1 is expressed at high levels in many cancers (24,25,29,30), humanization of a mouse allele could be of future use for preclinical in vivo HIP1-targeted drug testing. Second, this type of humanization addresses the question of whether the many introns of the large, 250-kb Hip1 locus are required for regulation of the Hip1 gene.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the conditional nature of this allele that allows for expression of HIP1 in specific tissues at specific times, there were other potential advantages of this targeting strategy. First, since HIP1 is expressed at high levels in many cancers (24,25,29,30), humanization of a mouse allele could be of future use for preclinical in vivo HIP1-targeted drug testing. Second, this type of humanization addresses the question of whether the many introns of the large, 250-kb Hip1 locus are required for regulation of the Hip1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…Gdpd3 knockout mice show no changes in PC. Gdpd3 has lysophosphatidylcholine (LPC)-specific phospholipase D (lysoPLD) activity that can generate lysophospha-tidic acid (LPA) and choline (30,34). In the first step in the biosynthesis of phosphatidylcholine, choline is phosphorylated to generate phosphocholine (PC).…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the conditional nature of this allele that allows for expression of HIP1 in specific tissues at specific times, there were other potential advantages of this targeting strategy. First, since HIP1 is expressed at high levels in many cancers ( 24, 25, 35, 36 ), humanization of a mouse allele could be of future use for preclinical in vivo HIP1 targeted drug testing. Second, this type of humanization addresses the question of whether the many introns of the large 250 Kb Hip1 locus are required for regulation of the Hip1 gene.…”
Section: Resultsmentioning
confidence: 99%
“…The role of HIP1 in leukemia (15) and lung cancer ( 20-22 ) as an oncogenic fusion partner and the necessity of Hip1 for mouse homeostasis are well established ( 11, 12 ). Additionally, HIP1 itself is upregulated in many cancers ( 24, 25, 35, 36 ) and prognostic in prostate cancer (25). However, mechanisms for how HIP1 overexpression contributes to transformation ( 24, 26 ) and how its deficiency in mice leads to degeneration are not known.…”
Section: Discussionmentioning
confidence: 99%
“…Analysis by western blot showed more than 50 cancer cell lines had high levels of HIP1 protein7. Similarly, overexpression of HIP1 gene was also observed in multiple human cancers including prostate cancer8, breast cancer9, brain tumor10, Merkel cell carcinomas11 and lymphoma12. Furthermore, in vitro analysis of the effects of HIP1 overexpression on cells indicated that it can transform fibroblasts9.…”
mentioning
confidence: 99%